WPŁYW OPODATKOWANIA NA WYBÓR FORMY INWESTYCJI BEZPOŚREDNIEJ W POLSCE - Jamroży, Marcin (Wydział Prawa i Administracji UAM, 2003)
The paper makes a comparison by means of the net terminal value method the current tax charges of two basic forms of direct investment, i.e. partnership/branch and company. The analysis shows that in the case of a German private businessman or partnership in Poland it is generally more advantageous in terms of tax to establish a partnership/branch than a company. This refers especially to highly profitable investments (i.e. yielding high profits in terms of absolute figures), since the size of the unwelcome progression effect is limited. Also in the aspect of e.g. loss settlement a partnership/branch has the benefit to settle the loss in Germany, which is beneficial due to the negative progression effect. The profitability of a certain investment project should not, however, be judged solely on the basis of the current taxation. During tax planning one should allow for a number of other factors, e.g. shape of mutual contractual relations (transfer prices), method of financing, dividend policy, taxation on occasional events, organizational structure, etc.
TAXATION AND CHOICE OF DIRECT INVESTMENT FORM IN POLAND